Fecal medicines used in traditional medical system of China: a systematic review of their names, original species, traditional uses, and modern investigations - Huan Du; Ting-ting Kuang; Shuang Qiu; Tong Xu; Chen-Lei Gang Huan; Gang Fan; Yi Zhang (BMC, 2019)
Abstract In China, the medical use of fecal matter (fresh fecal suspension or dry feces) can be dated back to the fourth century, approximately 1700 years ago. In long-term clinical practice, Chinese doctors have accumulated unique and invaluable medical experience in the use of fecal materials. In view of their good curative effect and medicinal potential, fecal medicines should be paid much attention. This study aimed to provide the first comprehensive data compilation of fecal medicines used in various Chinese traditional medical systems by bibliographic investigation of 31 medicine monographs and standards. A total of 54 fecal medicines were found to be used in 14 traditional Chinese medical systems. Their names, original species, medicinal forms, and traditional uses were described in detail. These fecal medicines were commonly used to treat gastrointestinal, nervous system, skin, and gynecological diseases. Commonly used fecal medicines include Wu-Ling-Zhi, Jiu-Fen and Hei-Bing-Pian. The information summarized in this study can provide a good reference for the development and utilization of fecal medicines. Further studies are necessary to prove their medicinal value, identify their active ingredients, and elucidate their mechanisms of action so that more people can accept these special medicines.